Dim Light at Night and Constant Darkness: Two Frequently Used Lighting Conditions That Jeopardize the Health and Well-being of Laboratory Rodents - González, Mónica M. C. (Frontiers in Neurology, 2018)
The influence of light on mammalian physiology and behavior is due to the entrainment of circadian rhythms complemented with a direct modulation of light that would be unlikely an outcome of circadian system. In mammals, physiological and behavioral circadian rhythms are regulated by the suprachiasmatic nucleus (SCN) of the hypothalamus. This central control allows organisms to predict and anticipate environmental change, as well as to coordinate different rhythmic modalities within an individual. In adult mammals, direct retinal projections to the SCN are responsible for resetting and synchronizing physiological and behavioral rhythms to the light-dark (LD) cycle. Apart from its circadian effects, light also has direct effects on certain biological functions in such a way that the participation of the SCN would not be fundamental for this network. The objective of this review is to increase awareness, within the scientific community and commercial providers, of the fact that laboratory rodents can experience a number of adverse health and welfare outcomes attributed to commonly-used lighting conditions in animal facilities during routine husbandry and scientific procedures, widely considered as “environmentally friendly.” There is increasing evidence that exposure to dim light at night, as well as chronic constant darkness, challenges mammalian physiology and behavior resulting in disrupted circadian rhythms, neural death, a depressive-behavioral phenotype, cognitive impairment, and the deregulation of metabolic, physiological, and synaptic plasticity in both the short and long terms. The normal development and good health of laboratory rodents requires cyclical light entrainment, adapted to the solar cycle of day and night, with null light at night and safe illuminating qualities during the day. We therefore recommend increased awareness of the limited information available with regards to lighting conditions, and therefore that lighting protocols must be taken into consideration when designing experiments and duly highlighted in scientific papers. This practice will help to ensure the welfare of laboratory animals and increase the likelihood of producing reliable and reproducible results.